Correlation of Kisspeptin-10 level and fetal well-being in preeclamptic patients - Maysoun A. Ziyaraa; Farqad B. Hamdan; Liqaa R. Mousa (Elsevier, 2016)
Objective: This study aims to evaluate the role of kisspeptin-10 in preeclampsia and check for possible relationship between its severity and fetal growth well-being. Kisspeptin-10 may participate in implantation of the embryo, placenta formation, and maintenance of pregnancy. Materials and Methods: One hundred women who completed 20 weeks of gestation with singleton pregnancies were divided into 60 peeclamptic and 40 normotensive control women. Kisspeptin-10 level estimation, and ultrasound and Doppler ultrasound studies for umbilical artery were performed during their second and third trimesters of pregnancy. Results: Plasma kisspeptin-10 level was lower in preeclamptic groups and inversely correlated with the severity of the disease. Its level directly correlated with estimated fetal weight in utero during both trimesters in patients with severe preeclampsia and with fetal birth weight in patients with mild preeclampsia, whereas an inverse correlation was observed in those with severe preeclampsia during their second trimester. Kisspeptin-10 level was directly related to the resistance index in the second trimester in patients with severe preeclampsia, while it inversely correlated with the systolic/diastolic ratio and resistance index in the third trimester in patients with mild preeclampsia. Conclusion: Kisspeptin-10 level is useful in assessing the severity of preeclampsia and can be a novel marker downregulated in pregnant women with preeclampsia, especially in those who also developed impaired uteroplacental perfusion or intrauterine growth restriction.